Cholestanol accelerates α-synuclein aggregation and spreading by activating asparagine endopeptidase - Ting Yu; Shuke Nie; Lihong Bu; Miao Liu; Juanfeng He; Xuan Niu; Hongyan Feng; Jifeng Guo; Beisha Tang; Zhaohui Zhang; Keqiang Ye; Haiqiang Jiang; et al. (JCI Insight, 2023)
Cerebrotendinous xanthomatosis (CTX), an autosomal recessive disorder characterized by high levels of cholestanol in the blood and accumulation of cholestanol in multiple tissues, especially the brain, often presents in parkinsonism. However, it remains unknown whether cholestanol plays a role in the pathogenesis of sporadic Parkinson’s disease (PD). Here, we show that the levels of serum cholestanol in patients with sporadic PD are higher than those in control participants. Cholestanol activates the protease asparagine endopeptidase (AEP) and induces the fragmentation of α-synuclein (α-syn) and facilitates its aggregation. Furthermore, cholestanol promotes the spreading of α-syn pathology in a mouse model induced by intrastriatal injection of α-syn fibrils. KO of AEP or administration of an AEP inhibitor ameliorates α-syn pathology, degeneration of the nigrostriatal dopaminergic pathway, and PD-like motor symptoms. These results not only indicate that cholestanol contributes to the aggregation and spreading of α-syn by activating AEP but also reveal an opportunity for treating PD with AEP inhibitors.